Improvement of modeling methods in rats with diabetic nephropathy and the expression level of IL-10 in kidney tissue - CAO Dong-dong; LI Niu; CAO Zi-yu; HOU Yu-long; NI Wen-juan; LENG Xiao-min; LIU Yun; SHI Jing-jing; Guo Ming-hao; MA Dong-hong (Linchuang shenzangbing zazhi)
Objective To improve the modeling method in diabetic nephropathy rats,and to detect the expression of IL-10 in kidney tissue.Methods Forty-eight male SD rats were randomly classified as normal control group(NC group,n=24)and diabetes group(DM group,n=24).In the DM group intraperitoneal injection of STZ at a dose of 40 mg/kg was performed one time to induce a diabetes model.Blood sugar,urine sugar,urinary microalbumin,urinary creatinine levels were detected at 0,4,8,12 weeks after successfully modeling,respectively.At the same time, the kidney pathology of rats at different time points was observed,and IL-10 expression levels was detected with immunohistochemical method.Results Compared with NC group,the modeling success rate of rats in the DM group was 75%,and the modeled rats showed significantly increased drink,food uptake and urine.By 12 weeks the average weight of rats in the DM group was(478.0±79.1)g,significantly lower than that in NC group(650.0 ±26.9)g.Blood glucose in the DM group(25.6±5.3)mmol/L was significantly higher than that in the NC group(5.2±0.2)mmol/L.Until the end of the experiment,it was found that blood sugar was still maintained at(23.0±5.5)mmol/L.In the DM group rats,urine microalbumin creatinine ratios at 8 weeks and 12 weeks were(39.0 ±18.6)mg/g and(77.0±12.3)mg/g,respectively,significantly higher than those in the control group(15.1±5.4)mg/g,(15.8±7.0)mg/g).Optical microscope observation indicated that DM group rat experienced renal interstitium edema and inflammatory cell infiltration at 0 weeks,and mild thickening of the glomerular base membrane and renal tubular epithelial vacuolar degeneration at 12 weeks.The results of immunohistochemistry showed that the expression of IL-10 in NC group was higher than that in DM group.Conclusions When high sugar and high-fat combined with a small dose of STZ are used to establish a DKD model,at 12 weeks the kidney has mild thickening of renal glomerular base membrane,vacuolar degeneration of renal tubular epithelial cells and other pathological changes.However,Blood glucose ≥16.7 mmol/L in the tail vein ≥16.7 mmol/L cannot be used alone to judge success of the modeling of DKD.The decreased expression of IL-10 in renal tissues further demonstrates that IL-10 is involved in the pathogenesis of DKD and may be the target of DKD treatment.